2013
DOI: 10.1093/nar/gkt129
|View full text |Cite
|
Sign up to set email alerts
|

Active regulator of SIRT1 is required for ribosome biogenesis and function

Abstract: Active regulator of SIRT1 (AROS) binds and upregulates SIRT1, an NAD+-dependent deacetylase. In addition, AROS binds RPS19, a structural ribosomal protein, which also functions in ribosome biogenesis and is implicated in multiple disease states. The significance of AROS in relation to ribosome biogenesis and function is unknown. Using human cells, we now show that AROS localizes to (i) the nucleolus and (ii) cytoplasmic ribosomes. Co-localization with nucleolar proteins was verified by confocal immunofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…SIRT1 is a deacetylase that is transcribed in response to caloric restriction . It regulates epigenetic gene silencing, inhibits the transcription of rRNA and subsequently reduces ribosome biogenesis . This occurs upon alterations of the NAD+/NADH ratio activating the energy‐dependent nucleolar silencing complex (eNoSC) containing Nucleomethylin (NML), SIRT1, and SUV39H1 to drive epigenetic changes on the rDNA locus that result in the repression of rRNA transcription .…”
Section: Sirt1 and Ribosome Biogenesismentioning
confidence: 99%
“…SIRT1 is a deacetylase that is transcribed in response to caloric restriction . It regulates epigenetic gene silencing, inhibits the transcription of rRNA and subsequently reduces ribosome biogenesis . This occurs upon alterations of the NAD+/NADH ratio activating the energy‐dependent nucleolar silencing complex (eNoSC) containing Nucleomethylin (NML), SIRT1, and SUV39H1 to drive epigenetic changes on the rDNA locus that result in the repression of rRNA transcription .…”
Section: Sirt1 and Ribosome Biogenesismentioning
confidence: 99%
“…Analyses were carried out as previously described (Knight et al 2013). Total RNA was isolated using TRIzol (Invitrogen) as per the manufacturer's instructions.…”
Section: Pre-rrna Northern Blottingmentioning
confidence: 99%
“…Additional study showed that SIRT1 activation by the endogenous active regulator of SIRT1 also attenuated eIF2α phosphorylation and regulated ribosome biogenesis. 27 These data suggested that coordination of deacetylation and dephosphorylation of eIF2α may also be critical for ISR signaling and cytoprotection.…”
mentioning
confidence: 92%